Biodiversity of Division Bryophyta (True Moss) in Kapas Biru Waterfall Pronojiwo Lumajang - Annisa Maharani; Pujiastuti .; Siti Murdiyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
Indonesia has a wide variety of of moss plants. Approximately 1500-2000 types of true moss and liverworts are found in Indoensian territory. Moss are commonly found in humid habitats, in climatic conditions of tropical forests and waterfalls such as Kapas Biru Waterfall Pronojiwo Lumajang. This descriptive explorative study aimed to identify moss species found in Kapas Biru Waterfall Pronojiwo Lumajang. The sampling area was divided into 3 regions based on topography ie parking area, along the footpath heading towards the waterfall, and the area around the waterfall. The study was conducted using cruise method and plotting method. Several environmental factors such as temperature, air and soil humidity, soil pH, light intensity, wind velocity and elevation. The result showed that there are 13 species of mosses found belonging to 11 different families. Keywords: Biodiversity, Bryophyta, Kapas Biru Waterfall.